'Extended' vocal techniques in the institution: The Extended Vocal Techniques Ensemble at the Center for Musical Experiment at UCSD. Issue 2 (17th January 2023) - Noble, Charissa
In the decades following the Second World War, novel sound technologies and the proliferation of ethnomusicological field recordings ignited curiosity and experimentation among many musicians; these cultural phenomena also sparked a re-examination of conventional Euro-American musical sound sources. Classically trained instrumentalists and singers – particularly those associated with the 'experimental tradition' – cultivated intentionally idiosyncratic musical practices and widened their range of sonic possibility; this cultural zeitgeist included a heightened interest in so-called extended vocal techniques. In this article, I examine the research and creative output of the Extended Vocal Techniques Ensemble (EVTE) of the University of California at San Diego (UCSD). Drawing from published literature, interviews and archival sources to write this account of the EVTE's multifaceted work, I contextualize the group's activities within UCSD's interdisciplinary emphasis as well as in the broader social–historical discourses of 'extended vocal techniques'. Furthermore, I address the implications of their story within the broader politics of vocal aesthetics and pedagogy in Euro-American classical music contexts. By unearthing the EVTE's interdisciplinary vision for vocal study, I hope to not only spark interest in this ensemble's contributions, but also to revive (and build upon) their vision of a radically reimagined vocal artistry and study in academic music and beyond.